POTENSI ANAK BERBAKAT DALAM NOVEL FRINDLE KARYA ANDREW CLEMENTS - Bintan, M. Ilham; Wantasen, Isnawati L.; Lasut, Theresia M.C (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  ABSTRACTÂ  Â  Â This research entitled â€œPotensi Anak Berbakat dalam Novel Frindle Karya Andrew Clementsâ€ is intended to fulfill a requirement to accomplish the Sarjana degree at Faculty of Humanities, Sam Ratulangi University, Manado. It aims at determining qualities of gifted child of Nick Allen as the main character in novel Frindle. Nick has many bright ideas; he is a good kid who solves problems around him. His traits that tend to be a gifted child can be found from him sitting in grade 2, this is supported by his environment from classmates to his teacher. This study uses the theory of Leta S. Hollingworth (1926), and uses a descriptive method in analyzing the data in the novel. The results show that the main character, Nick Allen, has tendencies as gifted children, such as leadership, sense of humor, courage initiative, obedience, studiousness, persistence, cheerfulness, intellectual modesty, and evenness of temper. That factors influence this are Nick's own environment, friends and family and even people use a word invention. It had such an unexpected impact that he became famous for his invention.Keywords: Gifted Child, novel Frindle